Presenteeism, Overcommitment, Workplace Bullying, and Job Satisfaction: A Moderated Mediation Relationship - Rodríguez-Cifuentes, Francisco (Int J Environ Res Public Health, 2020)
Presenteeism is a hazardous behaviour that may have personal and organizational consequences. The main objective of this research was to investigate the relationship between presenteeism and job satisfaction and evaluate the role of overcommitment as a mediator and the role of work-related and personal bullying as moderators in these relationships. Results from 377 subjects showed that presenteeism and overcommitment are positively related to job satisfaction, with overcommitment being a mediator in the relationships. These relationships are moderated by work-related bullying but not by personal bullying. The findings are discussed, and implications, future research pathways, and limitations are noted.